The Macroeconomy and the Yield Curve: A Nonstructural Analysis - Francis X. Diebold; Glenn D. Rudebusch; S. Boragan Aruoba (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
We estimate a model with latent factors that summarize the yield curve (namely, level, slope, and curvature) as well as observable macroeconomic variables (real activity, inflation, and the stance of monetary policy). Our goal is to provide a characterization of the dynamic interactions between the macroeconomy and the yield curve. We find strong evidence of the effects of macro variables on future movements in the yield curve and much weaker evidence for a reverse influence. We also relate our results to a traditional macroeconomic approach based on the expectations hypothesis.
urn:nbn:de:hebis:30-10365
Keywords: G1; E4; C5; 330; Yield curve; term structure; interest rates; macroeconomic fundamentals; factor model; state-space model